2018
DOI: 10.3390/ijerph15030432
|View full text |Cite
|
Sign up to set email alerts
|

Violent and Non-Violent Criminal Behavior among Young Chinese Drug Users: A Mixed Methods Study

Abstract: Young drug users are found to be increasingly involved in criminal justice issues. This exploratory and descriptive study aims to analyze the criminal behaviors among young Chinese drug users through a mixed methods research design. Quantitative analysis indicates that young drug users with and without a history of criminality show significant differences in terms of several features. Male drug users, particularly, those who are older, with religious beliefs, and initiated into drug use at younger age were mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Unlike us, this was done by our Chinese colleagues, who demonstrated that the use of drugs, street prostitution, crimes, and violence are the links of the same chain that can be broken be means of early criminological preventive measures and implementation of public anti-drug psycho-correctional programs (the specificity of which was not disclosed). We also had the opportunity to find confirmation of our own results, i.e., doctors from Beijing pointed out the important role of anxiety indicators both in the delinquent behavior of drug addicts and during the process of their rehabilitation (resocialization) [6]. We have to note that Chinese law enforcement officers, doctors and social workers consider in detail the issues of how preventive, restorative and punitive measures taken against drug addicts correlate with each other (such issues being discussed intensively for many years in the Russian Federation).G.Y.…”
Section: Discussionmentioning
confidence: 72%
“…Unlike us, this was done by our Chinese colleagues, who demonstrated that the use of drugs, street prostitution, crimes, and violence are the links of the same chain that can be broken be means of early criminological preventive measures and implementation of public anti-drug psycho-correctional programs (the specificity of which was not disclosed). We also had the opportunity to find confirmation of our own results, i.e., doctors from Beijing pointed out the important role of anxiety indicators both in the delinquent behavior of drug addicts and during the process of their rehabilitation (resocialization) [6]. We have to note that Chinese law enforcement officers, doctors and social workers consider in detail the issues of how preventive, restorative and punitive measures taken against drug addicts correlate with each other (such issues being discussed intensively for many years in the Russian Federation).G.Y.…”
Section: Discussionmentioning
confidence: 72%
“…This study also discussed the chain mediation between exercise self-efficacy and HRQoL. Long-term drug abuse leads to poor physical functioning, which is also the main factor affecting the psychological function of those with drug addiction (Liu Liu et al, 2018). The level of exercise self-efficacy has a reliable correlation with persisting exercise and has a negative correlation with psychological disturbance and physical discomfort (Hötting et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…The importance of violence during the adolescence as predictor of offending patterns in adulthood is still debated ( Cardwell and Piquero, 2018 ), even if violent behaviors during the childhood, for example the presence of aggressions ( Juon et al, 2006 ), seem to predict serious offending in adulthood. The link between drug use and criminal behavior has received attention from scholars ( Tonry and Wilson, 1990 ; Bennett et al, 2008 ; Gottfredson et al, 2008 ; Liu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%